Empowering sagon MSMEs through e-commerce education to support tourism in Magelang - Nur Hidayatulloh; Nurma Styarini; Resti Yunian; Indra Bayu Pangestu; Nur Muhammad Rosyada; Bagiyo Condro Purnomo; Suroto Munahar (Community Empowerment, 2024)
Culinary tourism serves as a strategic approach for the development of tourism in Magelang Regency, contributing to the realization of sustainable tourism. The growth of Micro, Small, and Medium Enterprises (MSMEs) is intertwined with the progress of the tourism industry in Magelang, emphasizing the crucial role of MSMEs in utilizing online media for effective promotion and product sales. This communtiny service aims to empower the Sagon Mbah Moel traditional food situated in Mantenan hamlet, Mertoyudan, Magelang, facilitating an increase in sales and promotion through digital marketing. The implementation method for this service activity is structured in two phases: preparation and execution. The service spanned approximately two months, with a primary focus on digital marketing training and the development of appealing product packaging. The outcomes include enhanced capacity and quality for Sagon Mbah Moel MSMEs. The positive impact of this service activity is evident in the initiation of product promotions and sales through digital marketing channels, as well as the improvement of product packaging and the maintenance of several production equipment.